2016
DOI: 10.1016/j.nrl.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Estudio piloto de un nuevo método de estimulación aritmética empleando el ábaco en ancianos sanos y con trastorno cognitivo

Abstract: The study suggests that cognitive stimulation with abacus arithmetic may be used in elderly people with and without cognitive impairment. Further studies will be needed to evaluate the efficacy of this kind of programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
0
13
0
4
Order By: Relevance
“…8 A number of studies based on cognitive stimulation have shown improvements in cognitive function in healthy older people, elderly with MCI and with dementia. [9][10][11][12][13][14][15] The findings of Alves et al 15 suggest that cognitive stimulation can lead to high values of experiential relevance, even in the absence of cognitive or functional improvements. The study of Schultheisz et al 16 supports cognitive stimulation programs as a resource for improving cognition and quality of life for the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…8 A number of studies based on cognitive stimulation have shown improvements in cognitive function in healthy older people, elderly with MCI and with dementia. [9][10][11][12][13][14][15] The findings of Alves et al 15 suggest that cognitive stimulation can lead to high values of experiential relevance, even in the absence of cognitive or functional improvements. The study of Schultheisz et al 16 supports cognitive stimulation programs as a resource for improving cognition and quality of life for the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…participants first learn how to manipulate the abacus and, after achieving proficiency, perform calculations using a mental image of the device, manipulating the beads of the mental abacus (MA). 20 One of the included studies 22 also applied a task using a physical abacus (PA). Seven studies showed an association between WM and AMC training.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 eligible studies were retrieved, whose objectives included investigating the effect of WM, 16,28,32 arithmetic performance, 16,28,29 short-term memory, 31 executive functions and underlying brain activity 17 and on brain networks, 28 and to determine the applicability of abacus use as a method of cognitive stimulation for older adults. 22 Cognitive training using abacus in children All 6 studies involving samples of children performed AMC interventions, in which a PA was used at only one stage to aid learning of AMC. 20,21,28,30 Five articles showed that AMC training promoted improved arithmetic skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos estudios nacionales [19][20][21][22] e internacionales [23][24][25][26][27] han demostrado beneficios cognitivos significativos en el campo del envejecimiento normal que pueden deberse en parte a la capacidad de reserva cognitiva 28 . Otros estudios han analizado la transferencia de su programa sobre la esfera emocional [19][20][21][22][29][30][31][32] y han investigado cómo influyen las variables sociodemográficas y clínicas neuropsiquiátricas sobre el mismo 19,21,22,29,31 .…”
Section: A H E a D O F P R I N T Introducciónunclassified